Konsep Dasar Konseling Catur Murti dalam Konteks Multibudaya - Amalda Amalda; Talitha Hasnabila Firjatullah; Nuris Sa’idah Rahmah Maulidiyah; Bakhrudin All Habsy (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2025)
Catur Murti Counseling integrates the concept of self-acceptance as a foundation that aims to provide a deep understanding of self-development and interpersonal relationships through a psychological approach. Catur Murti, which originates from Javanese culture, teaches the importance of balance in four aspects of life: spiritual, intellectual, emotional, and physical. By using qualitative research methods and using types of literature studies that aim to describe the facts that have been collected and then provide explanations and understanding of the facts regarding the concept of catur murti counseling. This counseling not only helps individuals understand themselves, but also in building harmonious relationships with others. Through counseling techniques based on the principles of Catur Murti, individuals are invited to explore their potential, overcome conflicts, and create a more meaningful life.